Green cloud computing : - Σαρρηγιάννης, Ιωάννης Κ. (2014)
This Diploma Thesis aims to provide knowledge, information and hands-on experience regarding the field of Cloud Computing services using Openstack at its 9th version AKA ICEHOUSE. Openstack is an open source IAAS platform that provides Virtual Machine services remotely via the Cloud. Using certain techniques, providing such services becomes both money-saving and eco-friendly, justifying the benefits of Green Cloud Computing over the use of traditional machines. Accessing Virtual Machines provided by Openstack, users can rent exactly as much Storage, RAM or CPU power as they need without having to invest on expensive equipment. Scalability feature offers the option of less or more power if needed. Furthermore, using live migration techniques, Virtual Machine Images can be transferred among Compute Nodes in order to cope with additional resources requests or conserve power and emit less CO2 at low traffic periods.